Hoplites : the classical Greek battle experience - Hanson, Victor Davis (Routledge, 1991)
Incorporating research found in ancient literary, iconographic, epigraphic, and archaeological sources, this book explores the experiences of the soldiers who conducted battle on the small plains of ancient Greece. The volume, which draws on the accumulated expertise of nine American and British scholars, emphasizes the actual techniques of fighting and practical concerns as the use of commands, music in warfare, the use of ""dog-tags"", and ritual on the battlefield